Diffraction technique for the inspection of injection moulded optical disc - Wen, Dong Fang. (2008)
Control of the micro-pit or groove geometry is of major importance in the injection moulded optical disk (CD, CDR and DVD) and also the mastering of the disc. Basically, the optical disk geometry can be described in terms of the pit (groove) depth, full width at half maximum (FWHM) and the wall angle. Looking from the side of opto-electrical quality, it is desired that the pits (groove) have a certain depth, width and wall angle, as defined according to the optical design. In cross section, the pit (groove) should be a well-formed trapezium. An optical inspection system has been developed that measures geometrical parameters of the pit and groove. This optical system was devised using a laser diffraction phenomenon. The spiral track of microscopic depressions (pit or groove) on the surface of optical disk was treated as a trapezium phase grating (in transmission mode), its transmittance profile is determined by the pit or groove structure, which generates a certain diffraction pattern. The analysis of this grating is based on the scalar theorem, the groove parameters are finally measured and calculated from diffraction efficiencies. Complex aperture function are the focus in this project, the Fourier transform techniques for optical imaging processing have been used, simulation of the diffraction efficiency vs the parameters of the pit or groove geometry has been done by MATLAB.